THE EFFECT OF PERFORMANCE ABILITY EXERCISES ACCORDING TO THE LIMB SYMMETRY INDEX (PREFERRED AND NON-PREFERRED LIMB) ON SOME TYPES OF MUSCLE STRENGTH, MECHANICAL VARIABLES AND PERFORMANCE OF YOUNG SHOT PUT THROWERS - Saad Jassim Jilab; Ammar Makki Ali (Universitas Negeri Jakarta, 2026)
Background. To identify the effect of the performance ability exercises according to the limb symmetry index (preferred and non-preferred limb) on some types of muscle strength, mechanical variables and achievement for young shot put. Objectives. The purpose of this paper is to preparing performance ability exercises according to the limb symmetry index (preferred and non-preferred limb) for young shot put throwers. Method. Performance ability exercises (strength and speed) were applied, which were built according to the limb symmetry index for the preferred and non-preferred limb (through a test in the exploratory experiment) for two months at a rate of three training units per week on the research sample of 10 young throwers from the Middle Euphrates region who compete in the races held by the Iraqi Athletics Federation for the 2024 sports season. They were randomly divided into two equal groups, and some types of strength and achievement were measured for the effectiveness of the shot put lifting and photographed to extract some biomechanical variables through photography. Results. The results showed that the performance ability exercises according to the limb symmetry index (preferred and non-preferred limb) used by the experimental group and the regular training used by the control group led to the development of some physical abilities, mechanical variables and achievement for young shot put, and that the development of some abilities for the two groups led to the positive impact on the development of some mechanical variables for young shot put throwers and thus the impact on the achievement of the two groups and the superiority of the experimental group over the control group in the impact on the development of some abilities and some mechanical variables and achievement for young shot put throwers through the results achieved as a result of training based on the limb symmetry index, which gave more training to the non-preferred limb, which gave preference and final achievement. Conclusion. The researchers recommend emphasizing that throwing and jumping activity training be directed to developing the achievement ability in its various forms, especially activities that depend on the ability element because it directly affects the mechanical variables associated with the skill performance of the activity and thus the positive impact on achievement.